Numerical Investigation for Enhancement of Heat Transfer in Internally Finned Tubes Using ANSYS CFX Program - Shakir, Ali; O, Ammar; Baqer, Nofil (Basrah Journal for Engineering Sciences, 2015)
In this study, a numerical investigation has been carried out for single phase flow behavior for thirty six internally finned tubes to demonstrate the effect of axial pitch to fin height ratio (p/e) for 0.8≤p/e≤6.345, helix angle of internal fins (β) for 30°≤β≤70°, apex angle of internal fins (α) for 0°≤α≤53.13°, internal fin height (e) for 0.6mm≤e≤1.0mm, internal tube diameter (di) with 14 mm and Reynolds number (Re) of single phase flow for 10000≤Re≤50000 on enhancement of forced convection heat transfer and reduction of friction factor by using ANSYS CFX program. It solves the three- dimensional Navier-Stokes equations for steady state turbulent with SST model and enhance wall treatment. The numerical analysis provided at fully developed velocity and temperature. Numerical results showed that the smallest axial pitch to fin height ratio (p/e) =0.8 and with apex angle α=10 degree provided enhancement of heat transfer of 2.8 to 3.55 times higher than of smooth tube. Finally, present numerical results are seen to be in good agreement with literature experimental correlations.